PENGARUH KLASIFIKASI INDUSTRI DAN BEBAN OPERASI TERHADAP LABA OPERASI (Studi Kasus Pada Industri Pertanian dan Aneka Industri Yang Terdaftar Di Daftar Efek Syariah Bursa Efek Indonesia) - Mey Maemunah; Raisa Umami (Fakultas Ekonomi UNIBBA, 2016)
This study aimed to analyze the effect of industry classification and operating expenses to income from operations for agriculture various industry listed on the Syariah Listing Stock, Indonesia Stock Exchange. This study considered quantitative research. The research sample was determined by purposive sampling method and study during the 2009-2012 period in order to obtain a sample of 8 companies. Type of data use dissecondary data obtained from www.idx.co.id.The analytical method usedis the correlation and multiple regression analysis, to analyze their individual correlation while using the t test statistic. To test the overall hypothesis using the F test statistic. The results of this study concluded (1) classification of industry enterprises that produce long-lasting has effect on income from operations for agriculture industry but has not effect for various industry, (2) operating expenseshave effect againstin come from operations for agriculture and various industry, (3) classification of industry and operating expenses have a low effect against income from operations for agriculture and various industry, (4) industrial classification variable on agriculture industry is negative (-) that mean contrary relation, long-lasting product will reduce income from operations. Therefore, in various industry the regression has a positive (+) that mean in the same direction between industrial calcification with income from operations, it mean long-lasting product will increase income from operations.(5) Operating expenses variable has a negative (-) regression with income from operations in agriculture industry and various industry, it means operating expenses will reduce income from operations., (6) correlation between industrial classification and operating expenses for income from operations is low in agriculture industry, therefore in various industry is very strong